Faktor-Faktor yang Mempengaruhi Pemilihan Model Bagi Hasil Pada Sektor Pertanian di Wilayah Karesidenan Madiun - Suyoto Arief Adib Susilo; Adib Susilo (Falah: Jurnal Ekonomi Syariah, 2019)
The purpose of this study was to determine whether socioeconomic factors, production factors, religiosity factors, and transparency factors influence the selection of agricultural production sharing models in the Residency of Madiun. This research is quantitative with multiple regression analysis. Based on the T-test, socioeconomic factors partially have a significant influence on the selection of agricultural production sharing models in the Madiun Residency of 3.701. Meanwhile, the factor of religiosity has a significant effect on the selection of agricultural production sharing models in the Madiun Residency with a significance level of 0.039. Furthermore, the factor of production does not have a significant effect with a significance level of 0.778. Finally, it is a factor that has a significant influence on the selection of revenue sharing models with a significance level of 0.008. While based on ANOVA test results, the F count of 10.288 with a significance level of 0.000 is smaller than 0.05, which means that socioeconomic, religiosity, production, and transparency factors simultaneously have an influence on the selection of revenue sharing models.